Pengaruh ROA, ROE, dan DER terhadap Harga Saham Sektor Consumer Non-Cylicals yang Terdaftar di BEI Periode 2020-2023 - Seger Santoso; Riza Elsiana (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The capital market serves as a forum for companies to obtain funds from investors, who in turn can benefit through dividends or stock price differences. The stock price itself is the value per share of a company traded on the stock exchange. This study aims to examine how Return on Assets, Return on Equity, and Debt to Equity Ratio relate to the stock prices of non-cyclical consumer sector companies on the Indonesia Stock Exchange from 2020 to 2023. The quantitative method with multiple linear regression was used to test this relationship using SPSS 25. Of the 47 companies taken as samples using purposive sampling method, this study found that Return on Assets and Debt to Equity Ratio have a negative impact on stock prices, while Return on Equity has a positive effect. Therefore, companies in this sector are advised to improve their Return on Assets and Return on Equity performance in order to increase their share price in the capital market.